Psychological Peculiarities of Civil Servant’s Professional Identity - Mudryk, Alla (Psychological Prospects Journal, 2015)
A professional identity combines the social and personality constituents of personality identity and becomes one of important factors in becoming a professional. The article examines the phenomenon of “professional identity” and its importance for the analysis of the civil servants’ professionalization. The analysis of domestic  and foreign scholars’ works on issues of professional identity has been made. The basic concepts such as “identity” and “professional identity” are under consideration. The research is defined by the fact that professional identity acts as an internal source of professional development and personal growth of any actor and the question of the development of professional identity is included into the total range of problems of any professional. In the article the conclusion has been made that a professional identity is an integrative concept that combines the cognitive, motivational, behavioral descriptions of personality and their values, which allow to become professionally orientated, to fulfill oneself in a profession, to forecast the prospect of a person’s development in the role of professional. A professional identity is one of basic indicators of professionalism and determined as identifying oneself with the selected type of activity. A professional identity combines the social and personality constituents of a personality identity and becomes one of important factors in becoming a professional. The article presents and analyses the results of empiric study of civil servants’ professional identity. The conclusion contains the characteristics of  professional identity of civil servants and level of its maturity, it outlines out some prospects for further research how to improve the methods of study of civil servant’s professional identity along with the aspects of constructing a harmonious environment for their professionalization.
Keywords: identity, professional identity, professionalism, personal identity, social identity, civil servant.